Enterprise Architecture Development to Strengthen Sustainability in the Supply Chain - Hindarto, Djarot (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
In contemporary international business, the significance of sustainability in supply chain operations has emerged as a prominent area of interest. The present study investigates the significant impact that Enterprise Architecture has on enhancing the sustainability of enterprise supply chains. By integrating Enterprise Architecture concepts in their entirety, this study presents a framework that empowers organizations to formulate sustainable sustainability strategies. Enterprise Architecture is utilized to identify, manage, and integrate supply chain critical elements that impact sustainability, such as waste management, energy efficiency, resource utilization, and the selection of sustainable business partners. This research demonstrates how progressive Enterprise Architecture implementation can contribute to the sustainability of supply chains, assist organizations in addressing environmental and social challenges, and generate long-term value for businesses and their business ecosystems by delineating an all-encompassing architecture. This study examines in depth how the application of Enterprise Architecture can catalyze achieving supply chain sustainability and provides companies with guidance on how to design and implement sustainable, structured sustainability strategies.